Impact of radiotherapy and sequencing of systemic therapy on survival outcomes in melanoma patients with previously untreated brain metastasis: a multicenter DeCOG study on 450 patients from the prospective skin cancer registry ADOREG : original research - Franklin, Cindy; Mohr, Peter; Bluhm, Leonie; Grimmelmann, Imke; Gutzmer, Ralf; Meier, Friedegund; Garzarolli, Marlene; Weichenthal, Michael; Pfoehler, Claudia; Herbst, Rudolf; Terheyden, Patrick; Utikal, Jochen; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Despite of various therapeutic strategies, treatment of patients with melanoma brain metastasis (MBM) still is a major challenge. This study aimed at investigating the impact of type and sequence of immune checkpoint blockade (ICB) and targeted therapy (TT), radiotherapy, and surgery on the survival outcome of patients with MBM. - Method We assessed data of 450 patients collected within the prospective multicenter real-world skin cancer registry ADOREG who were diagnosed with MBM before start of the first non-adjuvant systemic therapy. Study endpoints were progression-free survival (PFS) and overall survival (OS). - Results Of 450 MBM patients, 175 (38.9%) received CTLA-4+PD-1 ICB, 161 (35.8%) PD-1 ICB, and 114 (25.3%) BRAF+MEK TT as first-line treatment. Additional to systemic therapy, 67.3% of the patients received radiotherapy (stereotactic radiosurgery (SRS); conventional radiotherapy (CRT)) and 24.4% had surgery of MBM. 199 patients (42.2%) received a second-line systemic therapy. Multivariate Cox regression analysis revealed the application of radiotherapy (HR for SRS: 0.213, 95% CI 0.094 to 0.485, p<0.001; HR for CRT: 0.424, 95% CI 0.210 to 0.855, p=0.016), maximal size of brain metastases (HR for MBM >1 cm: 1.977, 95% CI 1.117 to 3.500, p=0.019), age (HR for age >65 years: 1.802, 95% CI 1.016 to 3.197, p=0.044), and ECOG performance status (HR for ECOG ≥2: HR: 2.615, 95% CI 1.024 to 6.676, p=0.044) as independent prognostic factors of OS on first-line therapy. The type of first-line therapy (ICB vs TT) was not independently prognostic. As second-line therapy BRAF+MEK showed the best survival outcome compared with ICB and other therapies (HR for CTLA-4+PD-1 compared with BRAF+MEK: 13.964, 95% CI 3.6 to 54.4, p<0.001; for PD-1 vs BRAF+MEK: 4.587 95% CI 1.3 to 16.8, p=0.022 for OS). Regarding therapy sequencing, patients treated with ICB as first-line therapy and BRAF+MEK as second-line therapy showed an improved OS (HR for CTLA-4+PD-1 followed by BRAF+MEK: 0.370, 95% CI 0.157 to 0.934, p=0.035; HR for PD-1 followed by BRAF+MEK: 0.290, 95% CI 0.092 to 0.918, p=0.035) compared with patients starting with BRAF+MEK in first-line therapy. There was no significant survival difference when comparing first-line therapy with CTLA-4+PD-1 ICB with PD-1 ICB. - Conclusions In patients with MBM, the addition of radiotherapy resulted in a favorable OS on systemic therapy. In BRAF-mutated MBM patients, ICB as first-line therapy and BRAF+MEK as second-line therapy were associated with a significantly prolonged OS.